2007
DOI: 10.1177/030802260707000506
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Ward-Based Art Group to Assess the Occupational Participation of Adult Acute Mental Health Clients

Abstract: The use of a ward-based art group to assess the occupational participation of adult acute mental health clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…In summary, research indicates that (a) the MOHOST is a valid indicator of factors that influence occupational participation across a range of service users, (b) subscale scores derived from the MOHOST are meaningful and valid, (c) therapists can use the MOHOST in a reliable and valid manner, and (d) the MOHOST subscales discriminate between service users at different functional levels and are adequately sensitive to detect change in service users (Kielhofner et al 2009, Pan et al 2011. Its use in mental health and related areas has been explored in recent years (Mitchell and Neish 2007, Hawes and Houlder 2010, Lee and Harris 2010.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, research indicates that (a) the MOHOST is a valid indicator of factors that influence occupational participation across a range of service users, (b) subscale scores derived from the MOHOST are meaningful and valid, (c) therapists can use the MOHOST in a reliable and valid manner, and (d) the MOHOST subscales discriminate between service users at different functional levels and are adequately sensitive to detect change in service users (Kielhofner et al 2009, Pan et al 2011. Its use in mental health and related areas has been explored in recent years (Mitchell and Neish 2007, Hawes and Houlder 2010, Lee and Harris 2010.…”
Section: Methodsmentioning
confidence: 99%
“…These reports typically covered two sides of A4 paper and proved helpful in explaining the unique contribution that occupational therapy offers within the multidisciplinary team. Using professional language that is easily understood by colleagues (Mitchell and Neish 2007), they have aided communication with other health disciplines to ensure that clients receive the appropriate treatment and assisted social care colleagues in making robust cases for scarce services and funding. The formulation of MOHOST reports also helped the participants to prioritise competing demands and decide whether continued intervention was necessary or whether it was sufficient to make recommendations to others.…”
Section: Doug Hawes and Daniel Houldermentioning
confidence: 99%
“…Returning to the key question of interest, the issue concerns use of the MOHOST-SOF as a standalone assessment versus the full MOHOST. The full MOHOST is clearly a clinically useful tool, and practitioners report it to be a relatively quick and easy to use assessment (Forsyth et al, 2011;Hawes and Houlder, 2010;Mitchell and Neish, 2007). This, however, comes at the cost of length of requirements for multiple observations.…”
Section: Discussionmentioning
confidence: 99%
“…The results were that the MOHOST demonstrated good construct validity, item separation reliability, and concurrent validity, and the authors concluded the MOHOST was suitable for research and clinical purposes. Other research has shown that therapists using the MOHOST report it to be useful, helpful when making decisions, supportive of occupation-focused thinking, and useful for structuring client-centred practice (Forsyth et al, 2011;Hawes and Houlder, 2010;Mitchell and Neish, 2007).…”
Section: Previous Research On the Mohostmentioning
confidence: 99%